Assessment of oral hygiene status and gingival diseases among school going children - Haider, Khushtar; Naqvi, Akbar (International Journal of Psychosocial Rehabilitation, 2020)
Dental caries stars appearing in early childhood in both genders. It is still a common health problem. The present study was conducted to assess oral hygiene status and gingival diseases among school going children. This study was conducted among 450 school going children age ranged 8-12 years of both genders. The oral hygiene status was evaluated by using oral hygiene index simplified (OHI- S). Loe and silness index assessed gingival status and Periodontal status was determined with Russell’s Periodontal index.8 years children had 82% decayed, 7.4% missing and 3.2% filled teeth. 9 years had 84.5% decayed, 6.3% missing and 8.4% filled teeth, 10years had 86.2% decayed, 3% had missing and 12% had filled teeth, 11 years had 80% decayed, 2.5%                                                                                                                           had missing and15% had filled teeth and 12 years had 81.5%decayed, 1.4% had missing and 10.4% had filled teeth. The mean DMFT/ dmft score >3 in children with 8 years was seen in 2%, I 8 years in 3.5%, in 10 years in 4%, in 11 years in 3.2% and in 12 years in 3.8% and score 0 was present in 90%, 91%, 87%, 88% and 86% in years 8, 9, 10, 11 and 12 years old children respectively. Gingival status was mild in 22%, mild in 45%, moderate in 30% and severe in 3%. RPI was negative in 24%, mild gingivitis in 50%, gingivitis in 26% and gingivitis with pocket destruction was seen in 0%. Authors found that the caries, gingival and periodontal diseases were quite higher in higher age group as compared to lower. However, overall oral hygiene status found to be good.